Unfinished nursing care in healthcare settings during the COVID-19 pandemic: a systematic review - Aysun Bayram; Stefania Chiappinotto; Alvisa Palese (BMC, 2024)
Abstract Background Unfinished nursing care is becoming increasingly more of a concern in worldwide healthcare settings. Given their negative outcomes, it is crucial to continuously assess those nursing interventions that are commonly postponed or missed, as well as the underlying reasons and consequences. The worldwide COVID-19 pandemic has made it difficult for health facilities to maintain their sustainability and continuity of care, which has also influenced the unfinished nursing care phenomenon. However, no summary of the studies conducted during the COVID-19 pandemic was produced up to now. The main aim of this study was to systematically review the occurrence of, reasons for, and consequences of unfinished nursing care among patients in healthcare settings during the COVID-19 pandemic. Methods Systematic review registered in PROSPERO (CRD42023422871). The Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement guideline and the Joanna Briggs Institute Critical Appraisal tool for cross-sectional studies were used. MEDLINE-PubMed, the Cumulative Index to Nursing and Allied Health Literature, and Scopus were searched from March 2020 up to May 2023, using keywords established in the field as missed care, unfinished nursing care, or implicit rationing. Results Twenty-five studies conducted mainly in European and Asiatic countries were included and assessed as possessing good methodological quality. The following tools were used: the MISSCARE Survey (= 14); the Basel Extent of Rationing of Nursing Care (= 1), also in its revised form (= 2) and regarding nursing homes (= 2); the Perceived Implicit Rationing of Nursing Care (= 4); the Intensive Care Unit-Omitted Nursing Care (= 1); and the Unfinished Nursing Care Survey (= 1). The order of unfinished nursing care interventions that emerged across studies for some countries is substantially in line with pre-pandemic data (e.g., oral care, ambulation). However, some interesting variations emerged at the country and inter-country levels. Conversely, labour resources and reasons close to the emotional state and well-being of nurses were mentioned homogeneously as most affecting unfinished nursing care during the pandemic. None of the studies investigated the consequences of unfinished nursing care. Conclusions Two continents led the research in this field during the pandemic: Europe, where this research was already well established, and Asia, where this research is substantially new. While unfinished care occurrence seems to be based on pre-established patterns across Europe (e.g., regarding fundamentals needs), new patterns emerged across Asiatic countries. Among the reasons, homogeneity in the findings emerged all in line with those documented in the pre-pandemic era.